PENGARUH INTERVAL TRAINING TERHADAP VO2 MAX PADA EKSTRA KURIKULER PENCAK SILAT PERSAUDARAAN SETIA HATI TERATE RAYON KHUSUS SMKN 1 NANGA PINOH - Kardianus Kardianus; Suyatmin Suyatmin; Nur Moh Kusuma Atmaja (STKIP Melawi, 2020)
Abstract: This research aims to know the effect of Interval Training on VO2 Max in the extracurricularPencak Silat Brotherhood Faithful Heart Terate Rayon Special smkn 1 Nanga Pinoh.This research includes pre-experiment, with the sample not separate. The experimental methodwith the sample does not mean that the research has a single sample group, measured twice, thefirst measurement is done before the subject ispretests,then treatment,which is finally closed witha second measurement (posttest). The design used in this study was